Clinical education for the health professions theory and practice - Nestel, Debra; Reedy, Gabriel; McKenna, Lisa; Gough, Suzanne (Springer Reference)
This book compiles state-of-the art and science of health professions education into an international resource showcasing expertise in many and varied topics. It aligns profession-specific contributions with inter-professional offerings, and prompts readers to think deeply about their educational practices.